We Are Forgotten: A Qualitative Descriptive Exploration of Social Inclusion-Exclusion Expectations and Experiences of Older Adults in Ghana - Paul Alhassan Issahaku (SAGE Open)
This study extends existing literature on the balance of tangible and intangible support and services that older adults require for their social inclusion and dignified aging. The study makes a contribution to current literature on older adults’ social exclusion-inclusion in the context of Ghana from the lenses of critical gerontology, social exclusion theory, and human rights. A qualitative description approach was adopted, with a purposive sample of 18 older adults who provided data in individual interviews, and the data were analyzed thematically. Although Ghana has made some policy efforts at ensuring the well-being of older adults, findings of this study suggest that many older Ghanaians are forgotten, socially excluded, and falling through cracks in the social safety net. For their social inclusion, older adults require tangible and intangible forms of support that enable them achieve adequacy with basic needs, and social participation. An important form of tangible support older adults need is care, where they are provided with adequate food, clothing, housing, and income. Intangible forms of support that older adults need include guaranteeing them access to health care services where costs (of treatment, laboratory examination, or prescription medication) are not a structural barrier, and by supporting them with mobility and social and civic participation, where they participate in decision making, perform meaningful social roles, and have opportunities for social interactions. Policy and practice implications of the findings are discussed.